Nitrogen (N) Fertilizer Measuring Instrument On Maize-Based Plant Microcontroller - Hendra Yufit Riskiawan; Taufiq Rizaldi; Dwi Putro S. Setyohadi; Tri Leksono (IAES Indonesia Section, 2017)
One of the growth factors of corn plant is fertilizer according to nitrogen fertilizer requirement. The identification of nitrogen fertilizer requirement in corn plant can be done by measuring the green leaf level using Color Leaf Manual, using TCS3200 color sensor combined with Arduino Uno Board microcontroller, and information. In this study a tool was created that could automatically measure the amount of fertilizer needed for corn per hectare. The results of the measurements displayed on the LCD 2x16 bits Micro made a measurement of fertilizer based on leaf color for corn plants. By taking the RGB value from the leaf that comes through the color sensor and then compared with the RGB value in the leaf color chart that has been saved in microcontroller will get the information of the fertilizer dosage needed. The level of truth of the measuring instrument of fertilizer can be categorized good enough with the level of accuracy reached 82%.